2004
DOI: 10.1097/00129492-200407000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Caspases, the Enemy Within, and Their Role in Oxidative Stress-Induced Apoptosis of Inner Ear Sensory Cells

Abstract: This review covers the general roles of members of the cysteine protease family of caspases in the process of apoptosis (programmed cell death) looking at their participation in both the "extrinsic" cell death receptor and the "intrinsic" mitochondrial cell death pathways. It defines the difference between initiator and effector caspases and shows the progression of caspase activations that ends up in the apoptotic cell death and elimination of a damaged cell. The review then presents what is currently know ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
69
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 28 publications
4
69
0
1
Order By: Relevance
“…[18][19][20] To date, 14 caspases have been identified that are broadly divided into two groups, initiator (caspase-6, -8, -9 and -10) and executioner (caspase-2, -3 and -7). 18,21,22 In NIHL, apoptosis resulting from activation of the extrinsic pathway (caspase-8) or the intrinsic pathway (caspase-9) has been observed. 12,13,15,16 These two pathways converge on caspase-3, the final executioner of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] To date, 14 caspases have been identified that are broadly divided into two groups, initiator (caspase-6, -8, -9 and -10) and executioner (caspase-2, -3 and -7). 18,21,22 In NIHL, apoptosis resulting from activation of the extrinsic pathway (caspase-8) or the intrinsic pathway (caspase-9) has been observed. 12,13,15,16 These two pathways converge on caspase-3, the final executioner of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of free radicals acts directly to destroy phospholipids and as signaling molecules to upregulate cell death pathways leading to apoptosis or necrosis (Davies, 1996;Greenlund, et al, 1995;Deshmukh and Johnson, 1997;Van De Water et al, 2004). The aim of this study was to test the hypothesis that a change in oxidative state and the formation of free radicals play an important role in deafferentationinduced cell death in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Caspases (CASP), with 14 known members, comprise a family characterized by highly conserved intracellular aspartate-specific cysteine proteases (Van De Water et al, 2004;Mittal et al, 2011). Two types are recognized in the CASP family: initiator caspases and effector caspases.…”
Section: Introductionmentioning
confidence: 99%
“…CASP-2, -8, -9, -10 are initiator caspases and CASP-3, -6, -7 are executioner caspases (Yu et al, 2009). CASP-4 and -5 are not currently classified as initiator or effector, because they are inflammatory enzymes that, in concert with CASP-1, are involved in T-cell maturation (Van De Water et al, 2004). CASP-14 is not involved in apoptosis or inflammation, but instead is involved in skin cell development (Yu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%